Desain Inovasi Pembelajaran Sosial Emosional Terhadap Motivasi Belajar Peserta Didik di Kelas XII Sekolah Menengah Atas - A, Aisyah; Layal, Nurul; H, Hetilaniar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Social and emotional learning is driven by the belief that developing students' academic abilities alone is not enough. Social and emotional aspects also need to be considered. Various studies show that social-emotional competence plays an important role in a person's learning process and life success. As educators who interact directly with students, we can observe low learning motivation caused by the lack of application of social-emotional learning in the classroom. This research aims to increase students' learning motivation through social-emotional learning. The method used is library/literature study, with data obtained from studies of journals, books and other relevant sources. The data that has been reviewed will be concluded according to the problem studied. The aim of this research is to provide understanding and knowledge about social-emotional learning in order to increase student motivation in the learning process.